The Concept of Hifz an-Nafs in Protecting Child Victims of Sexual Violance: A Comparative Study of Islamic Law and Positive Law in Indonesia - Imron Choeri; Amrina Rosyada; Novita Putri Mardiana (Journal of Feminism and Gender Studies, 2025)
This study explores the concept of Hifz an-Nafs (protection of life) in Islamic law and its relevance to the legal protection of children who are victims of sexual violence in Indonesia. Utilizing a qualitative-descriptive approach, the research compares Islamic legal norms with national legal frameworks, especially Law No. 35 of 2014 on Child Protection and Law No. 12 of 2022 on Sexual Violence Crimes. The findings indicate that although Hifz an-Nafs offers a holistic and moral-spiritual foundation for protecting the dignity and safety of children, its application in practice remains largely symbolic. In contrast, the implementation of national law, while structurally adequate, still suffers from exclusivity and access inequality. The study also identifies how social and ideological boundaries—such as religious conservatism, family honor, and community stigma—hinder victims’ access to justice and reinforce protection for perpetrators. These boundaries contribute to the fragmentation of communal protection mechanisms, weakening both legal enforcement and moral solidarity. This research emphasizes the need for an integrative model that combines Islamic ethical principles with the inclusiveness of modern legal systems to achieve effective and compassionate protection for children.